When Lifestyle Becomes a Threat: Emerging Health Challenges of the 21st Century - Judijanto, Loso (Oshada, 2025)
The shift in modern lifestyles has become one of the main risk factors contributing to the decline in public health, particularly in urban areas. This study aims to analyze the impact of lifestyle on the health status of individuals in the productive age group in major cities in Indonesia. A quantitative approach was employed using a survey method with questionnaires distributed to 100 respondents aged 18–55 years. Data were analyzed using SPSS software with validity tests, reliability tests, Pearson correlation, and multiple linear regression. The results show a significant negative relationship between lifestyle and health status (r = -0.526; p < 0.05). Physical activity and stress management were found to be the most influential lifestyle factors contributing to declining health. The study concludes that unhealthy lifestyles pose a real threat to public health in the 21st century. Behavior-based interventions and cross-sector promotion of healthy lifestyles must be strengthened to prevent the rising burden of non-communicable diseases.